P621 Lactose intolerance assessed by analysis of genetic polymorphism, breath test and symptoms in patients with inflammatory bowel disease. (27th May 2021) - Nardone, O M; Manfellotto, F; D'Onofrio, C; Rocco, A; Annona, G; Sasso, F; De Luca, P; Imperatore, N; Testa, A; de Sire, R; Biffali, E; Castiglione, F
Abstract: Background: Many patients with inflammatory bowel disease (IBD) make restriction of dairy products to control their symptoms. We aimed to investigate the prevalence of lactose intolerance assessed with hydrogen breath test (H-BT) in IBD patients in clinical remission with symptoms suggestive for lactose intolerance, compared to a sex- age- and BMI-matched control population. We further detected the prevalence of three single nucleotide polymorphisms of the lactase (LCT) gene: the lactase non persistence LCT-13910CC (genetic wildtype) and the intermediate phenotype LCT-22018AG, LCT-13910CT and we assess the correlation between genotype and H-BT Methods: We performed a prospective study enrolling IBD patients in clinical remission: Crohn disease (CD) activity index CDAI<150 for CD and pMayo score≤1 for ulcerative colitis (UC) and controls. All of them underwent clinical evaluation, H-BT and genetic test analysing lactase gene polymorphisms located on chromosome 2. Statistical analysis was performed using chi-square, Student's t-test and ANOVA. Results: A total of 54 IBD patients and 69 matched controls were enrolled. H-BT was positive in 35(64.8%) IBD patients and 43 (62.3%) controls (p=0.3). No significant difference in lactose intolerance rate, assessed by H-BT and symptoms, was found between CD and UC patients (p =0.8). The wild-type genotype was found in 46 (85.2%) IBD patients, CT22018, AG13910 and CT22018/AG13910 polymorphisms were found in 9.3%, 1.8% and 3.7% respectively. While in the control group, the wild-type genotype, CT22018, AG13910 and CT22018/AG13910 polymorphisms were found in 87%, 5.8%, 5.8% and 1.4% of cases, respectively. The wild type and polymorphisms' prevalence did not differ between IBD population and control group (85.2%vs 87%, p=0.1) (14.8% vs 13%, p=0.7) [Fig.1] and between CD and UC (p>0.05) [Fig.2]. The correlation between positive H-BT and genetic analysis showed that the wild-type genotype was associated with higher rate of lactose intolerance in the total population (OR 5.31, 95%CI 1.73–16.29, p=0.003) and in the IBD population (OR 7.61, 95%CI 1.36–42.7, p=0.02), even thought not in the control group (OR 4, 95%CI 0.90–17.68, p=0.07) Fig.1 Fig.2 Conclusion: The prevalence of lactose intolerance in IBD is high but not dissimilar from that of the general population. The prevalence of the wild-type genotype in patients with IBD does not differ from the general population and it correlates with higher rate of lactose intolerance assessed with H-BT. Despite suggestive symptoms, about 1/3 of IBD patients is not lactose intolerant, not needing elimination diet. These can lead to promote a rationale and balanced dietary management in IBD and thereby preventing the occurrence of calcium phosphate metabolism disorders.